Managing Agricultural Expansion and Grazing Systems: Land-Use Conflicts in the SOFIA Region of Madagascar - Vahinimalala Tahinarizafy Angelo; Soameva Léa; Koto Bernard (Universitas Islam Negeri Mataram, 2026)
This study aims to examine the drivers of land struggles in the SOFIA region of Madagascar by analyzing how agricultural expansion, grazing practices, and governance dynamics shape conflicts between farmers and herders within rural land-use systems. The study adopts a qualitative research design. Primary data were collected through semi-structured interviews with 35 participants, including farmers, herders, and local authorities. Data were analyzed using inductive thematic analysis to identify recurring patterns in land use, governance, and livelihood management. The findings reveal competition over fertile land, the expansion of cash-crop agriculture, restricted grazing mobility, ambiguous land-tenure arrangements, and limited governance capacity, collectively intensifying land-related disputes. These challenges are further exacerbated by socioeconomic vulnerability and demographic pressures in communities that depend heavily on land-based agricultural and livestock livelihoods. This study contributes original insights by integrating agricultural and grazing practices with governance and livelihood management perspectives in an understudied region of Madagascar. It advances understanding of land-use conflicts by highlighting the interaction between rural enterprise activities, tenure insecurity, and local governance, offering context-specific implications for sustainable land management and conflict mitigation